2017
DOI: 10.3389/fnbeh.2017.00062
|View full text |Cite
|
Sign up to set email alerts
|

Change of Rin1 and Stathmin in the Animal Model of Traumatic Stresses

Abstract: The molecular mechanism of fear memory is poorly understood. Therefore, the pathogenesis of post-traumatic stress disorder (PTSD), whose symptom presentation can enhance fear memory, remains largely unclear. Recent studies with knockout animals have reported that Rin1 and stathmin regulate fear memory. Rin1 inhibits acquisition and promotes memory extinction, whereas stathmin regulates innate and basal fear. The aim of our study was to examine changes in the expression of Rin1 and stathmin in different animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…SDS induced no significant difference in total STMN1 expression among the four brain regions in the control, unsusceptible, and susceptible groups of WT mice. STMN1 expression in the AMY and HIP reportedly decreased after a single prolonged stress treatment and immobilization stress in rats [40]. In contrast, pS16- STMN1 expression levels significantly decreased in the PFC of unsusceptible and susceptible groups of WT mice compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…SDS induced no significant difference in total STMN1 expression among the four brain regions in the control, unsusceptible, and susceptible groups of WT mice. STMN1 expression in the AMY and HIP reportedly decreased after a single prolonged stress treatment and immobilization stress in rats [40]. In contrast, pS16- STMN1 expression levels significantly decreased in the PFC of unsusceptible and susceptible groups of WT mice compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Strongly involved in forming emotional memories, especially fear-related memories, the amygdala is thus regarded as the central brain region and attracts many scientists’ special attention. Using animal model of PTSD, previous studies have found that glucocorticoid receptor ( Kohda et al, 2007 ), 5-HT 2 C ( Harada et al, 2008 ), Rin1 and Stathmin ( Han et al, 2017 ), beta-adrenoreceptors ( Ronzoni et al, 2016 ), and beta-arrestin-2 ( Ding et al, 2017 ) are involved in the PTSD-associated behaviors. Besides, the amygdala is composed of several functionally distinct nuclei that interact during stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Exaggerated of the amygdala activity has been observed in response to trauma-related stimuli ( Shin et al, 1997 ; Liberzon et al, 1999 ; Pissiota et al, 2002 ; Hendler et al, 2003 ), and also during acquisition of conditioned fear ( Bremner et al, 2005 ). Using animal model of PTSD, a few studies found that 5-HT2C ( Harada et al, 2008 ), Rin1 and Stathmin ( Han et al, 2017 ), beta-adrenoreceptors ( Ronzoni et al, 2016 ), Neuropeptide S ( Cohen et al, 2018 ), and beta-arrestin-2 ( Ding et al, 2017 ) may be implicated in PTSD associated behaviors. Recently, through using c-Fos or other markers of neuronal activity, increased activation of the amygdala was found to be associated with traumatic stress-induced behavioral changes, such as anxiety-like behaviors and deficit in fear extinction ( Muigg et al, 2008 ; Hoffman et al, 2014 ; Ritov et al, 2014 ; Yu et al, 2015 ; Knox et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…SPS mimics many aspects of the pathophysiological abnormalities associated with PTSD, and also some aspects of the behavioral characteristics. 20,21 For instance, SPS rats exhibit enhanced glucocorticoid negative feedback, 22 sleep abnormalities, 23 enhanced anxiety, [24][25][26] hyperarousal 27 and enhanced contextual freezing 28 as well as the expected therapeutic response to long-term treatment with paroxetine on enhanced fear memory. 29 Several studies have showed impaired fear extinction in SPS rats, 30,31 which is alleviated by repeated administration of D-cycloserine 32 or by single administration of vorinostat, a histone deacetylase inhibitor.…”
mentioning
confidence: 99%